The Relationship of Emotional Intelligence with the Quality of Life of Diabetes Mellitus Patients in West Purwokerto Health Center - Oktaviani, Catur Resti; Siwi, Adiratna Sekar; Aprilliyani, Ita (Faculty of Medicine, Universitas Tadulako, 2025)
Background: The quality of life of Diabetes Mellitus (DM) patients is an essential aspect that must be considered throughout the treatment process. Psychological factors significantly influence the quality of life and can be better managed if patients possess good emotional intelligence. Objective: This study aimed to determine the relationship between emotional intelligence and the quality of life of DM patients at the Purwokerto Barat Health Center. Methods: This quantitative study employed a correlational analytic design with a cross-sectional approach. A total of 115 DM patients were selected using proportionate stratified random sampling. Data were collected using the Emotional Intelligence Scale (EIS) and the Diabetes Quality of Life (DQOL) questionnaire. Data analysis was performed using the chi-square test. Results: The majority of DM patients were elderly (81.7%), female (65.2%), had a basic education level (51.3%), had an income below the regional minimum wage (90.4%), had an average disease duration of 77.41 months (6.2 years), and had no other complications (71.3%). Most patients had good emotional intelligence (92.2%) and good quality of life (93%). Conclusion: There is a significant relationship between emotional intelligence and the quality of life of DM patients at the Purwokerto Barat Health Center.